Application of ionic liquids and various carbon materials in reference electrodes with carbon paste-based transducers - Kuczak, Julia; Woszczyk, Wiktoria; San H'ng, Paik; Li Lee, Chuan; Mohd Sahfani Mohd Nor Hafizuddin, Bin; Ling Chin, Kit (John Wiley and Sons, 2023)
In this article it is proved that carbon pastes with ionic liquids (ILs) are a promising material for transducers of reference electrodes, which favors their miniaturization. Two ILs were used: 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (IL1) and 1-(2-methoxyethyl)-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (IL2). They acted both as a binder of carbon paste and potential-determining component. ILs were also used in polymeric membrane of reference electrodes what ensured continuity of IL phase between carbon paste and the polymeric membrane and resulted in enhancement of electrode potential stability. It was shown that application of IL as a carbon paste binder is superior to conventional plasticizer and allows for significant increase of reference electrode potential stability. Different types of carbon materials were also tested during research: commercialy available graphite powder and graphene oxide obtained from waste biomass – palm kernel shells. It was observed that both the type of carbon paste material and IL influences reference electrode work parameters. Utilization of IL with less lipophilic cation resulted in higher potential stability of the reference electrodes. Application of graphite paste-based transducers resulted in higher potential stability of reference electrodes in sodium perchlorate and TMA chloride solutions while using palm kernel shell graphene oxide paste – based transducers caused enhancement of reference electrode long-term potential stability. The results indicate biomass-derived graphene oxide can be successfully applied as a construction material of reference electrode.